Konsentrasi Protein dan Asam Amino pada Ikan Gabus (Channa striata) yang Diberi Daging Keong Mas (Pomacea sp) Segar atau Kering - Jumriati, Jumriati; Idris, Muhammad; Yusnaini, Yusnaini (JSIPi (Jurnal Sains dan Inovasi Perikanan) (Journal of Fishery Science and Innovation), 2018)
This study aims to determine the concentration of protein and amino acids in Snakehead that are given apple snail fresh or dried. Used Snakehead with a total length of 7-10 cm and average initial weight of 5 g of 60 heads. Fish kept in a circular concrete tub with a diameter of 80 cm and height 50 cm, filled with water as much as 100 liters, then fish stocked density 10 tail/unit. Fish feeding test is done 2 times a day at 06.00-07.00, and 17.00-18.00. Apple snail are given 15% of the fish body weight of Snakehead. Variables of this study, absolute growth, protein retention, changes in amino acid composition of Snakehead. The results showed that after maintenance of 60 days of absolute growth of Snakehead by giving fresh apple snail (2.79 ± 1.21 g) and was given dried apple snail (1.87 ± 0.92 g). Protein retention in Snakehead with fresh apple snail (1.31 ± 1.42%), and with dried mask (0.37 ± 0.82%). A total of 15 amino acids obtained in Snakehead are divided into 8 essential amino acids namely, lysine, leucine, arginine, threonin, phenylalanine, isoleucine, valine and histidine, and 7 non essential acids ie glutamic acid, aspartic acid, alanine, glycine, tyrosine, serine, and proline. Lysine is the highest amino acid, Snakehead with fresh apple snail meat while the limiting amino acid is proline, either in Snakehead which is given fresh apple snail snacks or Snakehead which is given dried apple snail meat. Research can be concluded that giving fresh apple snail meat effect on growth and high protein retention in Snakehead. Total amino acids and essential amino acids in Snakehead are preferable by administration with dried snails.Keywords : Proteins, Amino Acids, Essential Amino Acids, Nonessential Amino Acids, Snakehead, Apple Snail